Problematika the New Cold War: Dinamika Geopolitik, Ekonomi dan Dampaknya Terhadap Stabilitas Asia Pasifik - Calyaretta Meiskha Wanodya; Yustine Juneytalenta; Arulina Firsta Ramadhina; Aurellia Zahra Ayundya (BELLI AC PACIS (Jurnal Hukum Internasional), 2024)
The new Cold War has been a hot topic of discussion recently–whether about its existence or how it was fought. The old Cold War was fought because of the clash of ideologies between the two superpowers; the United States and the USSR. Intellectuals argue that the new Cold War no longer involves ideology, as it no longer involves military hegemony. By limiting the problem to the Asia Pacific, the article focuses on the geopolitical and economic aspects of the related region. Through the research that has been conducted, the results were found to be; The Cold War that lasted from 1947–1991 was dominated by the ideological competition of Capitalism, led by the United States, and Communism, led by the Soviet Union. Meanwhile, the New Cold War focuses more on economic and geopolitical competition, especially between the United States and China. Also, the ineffectiveness of international law in enforcing decisions related to maritime disputes and global trade dynamics shows the need for stronger reforms.